The Effect of Perceived Service Quality and Consumer Satisfaction on User Loyalty for Grab-Bike Online Transportation - Zakiyyatul Fakiroh; Neno Sri Wahyuningsih; Putri Asmara Dirgantari; Khairani Zikrinawati; Zulfa Fahmy (Experimental Student Experiences, 2024)
This study aims to determine the effect of service quality and customer satisfaction on the loyalty of Grab-Bike online transportation users. The number of samples in this study were 100 people. Data analysis in this study used inferential quantitative analysis of multiple linear regression. In accordance with the data obtained, the results of the study show that service quality has no positive and significant effect on the loyalty of Grab-Bike online transportation users. Consumer satisfaction has a positive and significant effect on the loyalty of Grab-Bike online transportation users. Service quality and customer satisfaction together have a positive and significant effect on the loyalty of Grab-Bike online transportation users. Based on this evidence, the ability of the independent variables, namely service quality and customer satisfaction, has an effect of 35.1%, while the remaining 64,9% can be influenced by other variables not examined and analyzed in this study.